HUBUNGAN ANTARA DASAR-DASAR SEGMENTASI DENGAN KEPUTUSAN MASYARAKAT UNTUK BERGABUNG MLM DI KECAMATAN ILIR TIMUR II PALEMBANG - Akmal SS, Ahmad; Isnaini, Diah (Universitas muhammadiyah palembang, 2015)
The problem of this study was whether or not there was a significant correlation between fundamental segmentation with the decision to join MLM in Kecamatan Ilir Timur II Palembang. The objective of this study was to determine the significant correlation between fundamental segmentation withdecision of the community to join MLM in Kecamatan Ilir Timur II Palembang. This research was associative. The variables used in this study were the basics of segmentation, and decision to join. This study used were 100respondents as the sample. The sampling technique used was the snowball sampling (snowball sampling). The data required in this study was the primary data. The data collection technique used was questionnaires. Furthermore technique analysis used was Chi Square. The results found that the results of calculation using SPSS for Windows version 20.0 capitulation result obtained chi squared test calculations turned out mostly no relationship between the fundamental basis of segmentation with the decision to join the MLM community in the Kecamatan Ilir Timur II Palembang. There were only a few basic segmentations has correlation, such as the age of respondents to the time of join, marital status to the time of join, the respondents job to the kinds of MLM and the time of join MLM in Kecamatan Ilir Timur II Palembang.